2002
DOI: 10.1097/00042728-200205000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Topically Applied Avène Spring Water Spray in the Healing of Facial Skin after Laser Resurfacing

Abstract: background. Although laser resurfacing is a well-accepted treatment, tolerance problems may preclude patient's acceptance of the procedure. Post-laser protracted erythema is a prime problem, associated with the symptoms of pain, itching, stinging and tightening. objective. The present study was conducted to evaluate a low-salt medical spring water (Avène, Avène-les-Bains, France), in conjunction with the standard use of an emollient, to improve tolerance by hydrating the postlaser skin. methods. A controlled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…16 Moreover, clinical studies have confirmed the clinical interest of ATSW sprays in different irritation models with retinoic acid 17 or after skin procedures such as laser resurfacing. 11 Therefore, ATWS could be of interest after ALA-PDT procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Moreover, clinical studies have confirmed the clinical interest of ATSW sprays in different irritation models with retinoic acid 17 or after skin procedures such as laser resurfacing. 11 Therefore, ATWS could be of interest after ALA-PDT procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Several comparative clinical studies have shown that the use of Avène thermal spring water (ATSW) after a superficial irritating procedure such as PDT, and more aggressive procedures like laser resurfacing and strong peelings, decreases inflammation, reduces irritation, and improves patient discomfort. ATSW's therapeutic properties involve the reduction of cell sensitivity, thereby reducing the reactivity threshold 11 . ATSW also exhibits anti‐inflammatory properties by modulation of the body's natural immune defense mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In a French controlled, randomized clinical trial, treatment of facial skin with low-salt spring water spray and petrolatum ointment after laser resurfacing resulted in decreased itching, stinging, erythema, and tightening than treatment with petrolatum alone over a period of 84 days. 25 The efficacy of scar hydration strategies in these human trials is supported in the rat model, where one study revealed that carbon dioxide laser burn wounds healed more quickly with composite polyurethane dressings (i.e., OpSite, Smith & Nephew, Hull, U.K.; Spandra, Thermetics, Inc., Woburn, Mass.) (10 days) and petrolatum gauze (13 days) than when they were left open to air (16 days).…”
Section: Pressure Dressingsmentioning
confidence: 99%
“…Several comparative clinical studies have shown that the use of a particular thermal spring water (TSW) after superficial procedures such as photodynamic therapy, 7 and more aggressive laser resurfacing and medium/deep chemical peel procedures, decreases inflammation, reduces irritation, and improves patient discomfort. The therapeutic properties of the water involve the reduction in sensitivity of cells thereby reducing the reactivity threshold 8 . It also exhibits anti‐inflammatory properties by modulation of the body’s natural immune defense mechanism.…”
Section: Introductionmentioning
confidence: 99%